Cyanotoxins: A hidden cause of Chronic Kidney Disease of unknown etiology (CKDu) in Sri Lanka - A review - Manage, P. M (Sri Lanka J. Aquat. Sci., 2019)
CKDu has been identified as a major public health issue in countries such as Sri Lanka, India and Nicaragua, which causes significant deaths per year. Significant similarities have been observed among these endemic nephropathies regardless of their geographical separation. Existing evidence favors a multi-factorial etiology, but research over the last few decades has failed to recognize the specific risk factors. Based on the geographical distribution that is unique and evidence of histopathological nature, it is speculated that CKDu is environmentally induced health problem. Hypothesis linking acetylcholinesterase (AChE) inhibiting organophosphate pesticides, metal-chelating glyophosate, agrochemicals, cadmium, arsenic, fluoride, hardness, and algae/cyanobacteria are considered as important factors in the etiology of CKDu. However, to date, no single geochemical parameter is shown to be directly related to the CKD etiology on the basis of the elements determined during research studies, and it is very likely that the unique hydrogeochemistry and microbiology of the drinking water is closely associated with the incidence of the disease in the endemic areas. The paper discuss understudied area of research is whether cyanotoxin formation from algal blooms may be a risk factor that contributes to CKDu in Sri Lanka as cyanotoxins in CKDu has been considered but not investigated.
Keywords: cyanobacteria, cyanotoxins, environmental exposure, cell culture studies, cyto toxicity